Dulce de leche: Product types, production processes, quality aspects and innovations minor EDITS. (27th January 2021) - Vargas, Maryella Osório; Prestes, Amanda Alves; Miotto, Marília; Prudêncio, Elane Schwinden
Abstract : This article provides information regarding dulce de leche, a dairy product obtained by heating milk and sugar under controlled conditions. Some denominations of this product, and the physicochemical and microbiological parameters defined by legislation are also presented. Dulce de leche has three main forms of production with fewer common varieties; their differences are reported and highlighted. Adjuvants used in the process are detailed as well, due to their importance in the process and their influence on the final product's characteristics. Furthermore, innovations in dulce de leche production are also discussed. Abstract : This study approaches the types of dulce de leche and its production processes covering aspects of quality and technological innovation.